Theonymie celtique, cultes, interpretatio : = : Keltische Theonymie, Kulte, interpretatio : X Workshop F.E.R.C.A.N., Paris 24.-26. Mai 2010 - De Bernardo Stempel, Patrizia; Hofeneder, Andreas (2013)
Annotation